Anticancer Drug-Induced Acute Kidney Injury - Izzedine, Hassan (Kidney Int Rep, 2017)
Acute kidney injury (AKI) is a growing problem with untoward economic and medical consequences. Anticancer drug toxicity remains an important and increasing cause of AKI. Importantly, drug-induced AKI affects all nephron segments—vasculature, glomerulus, tubules, and interstitium. Recent studies have increased insight into the subcellular mechanisms of drug-induced AKI that include direct cellular toxicity and immune-mediated effects. Identification of patients with high-risk cancer before drug exposure may allow prevention or at least a reduction in the development and severity of nephrotoxicity. Recognition of drug-induced AKI and rapid discontinuation (or dose reduction) of the offending agents, when appropriate, are critical to maximizing kidney function recovery. Preventive measures require understanding patient and drug-related risk factors coupled with correcting risk factors, assessing baseline kidney function before initiation of therapy, adjusting the drug dosage and avoiding use of nephrotoxic drug combinations.